Correction: Light-induced in situ chemical activation of a fluorescent probe for monitoring intracellular G-quadruplex structures. Issue 1 (7th December 2022) - Deiana, Marco; Mosser, Maëlle; Chamignon, Cécile; Le Bahers, Tangui; Dumont, Elise; Dudek, Marta; Denis-Quanquin, Sandrine; Sabouri, Nasim; Andraud, Chantal; Matczyszyn, Katarzyna; Monnereau, Cyrille; Guy, Laure
Abstract : Correction for 'Light-induced in situ chemical activation of a fluorescent probe for monitoring intracellular G-quadruplex structures' by Marco Deiana et al., Nanoscale, 2021, 13, 13795–13808, ; https://doi.org/10.1039/D1NR02855C .